KONSEP INDEPENDENSI KEJAKSAAN REPUBLIK INDONESIA DALAM PERSPEKTIF TEORI THE NEW SEPARATION OF POWER BRUCE ACKERMAN - Sarah Nur Annisa (JIL : Journal of Indonesian Law, 2021)
Independence is a must in a state of law (rechtstaat) as stated in article 1 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The independence is inseparable from the theory of separation of powers. The separation of powers theory was developed by Charles Louis de Secondat Baron Montesquieu or better known as the trias politica theory which divides power into three, namely executive power, legislative power, and judicial power. The 1945 Constitution does not explicitly explain the existence of the prosecutor's office, but in Law no. 16 of 2004 which regulates the Attorney General's Office of the Republic of Indonesia places this institution as a "government institution" so that the position of the prosecutor in the Indonesian constitutional system is part of the executive power. This may causes the prosecutor's office to be independent and carry out its duties and functions. This study is a qualitative research, while the research approach used is the legal approach and the conceptual approach. Both the primary and secondary data was collected. The data was obtained through the 1945 Constitution, Law no. 16 of 2004, journals and books related to topic of research. The theoretical framework was applied to examine the concept of the independence of the Indonesian Attorney General Office by using the theory of The New Separation of Powers, which was initiated by Bruce Ackerman. In his theory, Ackerman divides powers into five, one of which is Independent Agencies. The result of this study showed that the position of the prosecutor's office is institutionally under executive power as stated in the prosecutor's law and regarding the ideal concept of prosecutor's independence in the Indonesian constitutional system which is analyzed through the theory of The New Separation of Power, namely by placing the prosecutor's office as an independent state institution that free from executive influence, broadly speaking, the placement of independent state institutions (Independent Agencies) is a separate branch of power out of the trias politica concept.